INOCULATION OF BRASSICA NAPUS L. GENOTYPES WITH ENDOPHYTIC BACTERIA PROMOTE GROWTH AND ALLEVIATE CADMIUM TOXICITY - A. U. Shah; H. Rajab; A. Jalal; M. Ajmal; S. A. K. Bangash; D. Ahmad; M. S. Khan (Journal of Animal and Plant Sciences, 2020)
Cadmium is a non-essential heavy metal that is highly toxic for most of the plants, even at low concentrations. Cadmium tolerant endophytic bacteria isolated from different sources have been effectively used for mitigating cadmium toxicity and plant growth promotion. In the present study, the potential of an endophytic bacterial strain known as Serratia sp. IU01, previously isolated from Solanum nigrum, was evaluated in terms of alleviating cadmium toxicity and promoting host plant growth. A significant increase in the biomass of two genotypes of Brassica napus L. exposed to different concentrations of cadmium was observed after three weeks inoculation with Serratia sp. IU01 compared to sole cadmium treated plants. High performance liquid chromatography (HPLC) analysis revealed the steady-levels of one of the key antioxidants, i.e., glutathione, were significantly higher in the sole cadmium treated plants compared to control plants. However, inoculation of the cadmium treated plants with the bacterial endophyte resulted in a significant reduction in glutathione contents compared to sole cadmium treated plants, which suggest the antioxidants released by the endophyte in the host environment have assisted the host plant in minimizing the magnitude of the resultant oxidative damage. The precursor of glutathione, i.e., cysteine, showed a similar pattern in the sole cadmium treated and inoculated plants. Our data suggested that inoculation of Brassica napus with the bacterial isolate Serratia sp. IU01, under cadmium stress provide a physiological advantage to the plants in terms of growth promotion and alleviating cadmium toxicity.
Keywords: Brassica napus; endophytes; cadmium; tolerance; stress